2013
DOI: 10.1016/j.jns.2013.07.720
|View full text |Cite
|
Sign up to set email alerts
|

Rotational vertebral artery occlusion: Mechanisms and long-term outcome

Abstract: Background and Purpose-To elucidate the mechanisms and prognosis of rotational vertebral artery occlusion (RVAO). Methods-We analyzed clinical and radiological characteristics, patterns of induced nystagmus, and outcome in 21 patients (13 men, aged 29-77 years) with RVAO documented by dynamic cerebral angiography during an 8-year period at 3 University Hospitals in Korea. The follow-up periods ranged from 5 to 91 months (median, 37.5 months). Most patients (n=19; 90.5%) received conservative treatments. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 16 publications
4
31
0
2
Order By: Relevance
“…Most patients with RVAO exhibit a stenosis of one VA while the dominant VA is compressed during contraversive head rotation, which compromises the blood flow in the vertebrobasilar region. 5,7 Alteration of local flow fields at the prone position, which is a frequent sleeping posture for many subjects and patients, could have important consequences in the tensile stress distribution around atherosclerotic plaques commonly found at the VJ. 29 Hemodynamic changes in VAs associated with head rotation may also play a role in the subclavian steal syndrome (SSS), which is defined as a group of symptoms that arise from the reversed blood flow in the VA when there is a stenosis in the ipsilateral subclavian artery.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with RVAO exhibit a stenosis of one VA while the dominant VA is compressed during contraversive head rotation, which compromises the blood flow in the vertebrobasilar region. 5,7 Alteration of local flow fields at the prone position, which is a frequent sleeping posture for many subjects and patients, could have important consequences in the tensile stress distribution around atherosclerotic plaques commonly found at the VJ. 29 Hemodynamic changes in VAs associated with head rotation may also play a role in the subclavian steal syndrome (SSS), which is defined as a group of symptoms that arise from the reversed blood flow in the VA when there is a stenosis in the ipsilateral subclavian artery.…”
Section: Discussionmentioning
confidence: 99%
“…23 These symptoms may be attributable to asymmetrical excitation of the bilateral labyrinth induced by transient ischemia or by disinhibition from inferior cerebellar hypoperfusion. 7 Affected patients classically exhibit stenosis or anomaly of the vertebral artery on the affected side, with hypoplasia or termination of the contralateral vertebral artery in the PICA. The dominant vertebral artery, thus, becomes compressed at the C1-2 level during contralateral head rotation resulting in compromised blood flow and subsequent ischemia.…”
Section: Bilateral Dynamic Arterial Compressionmentioning
confidence: 99%
“…In 2013, Choi et al 7 reported on 21 patients with rotational vertebral artery occlusion. One case involved a 37-year-old man with fainting spells and blurred vision, who had bilateral compression at C1-2.…”
Section: Fig 6 Right Vertebral Artery Injection Angiogram Obtained mentioning
confidence: 99%
“…RVBI is also known as Bow Hunter's Syndrome and is most classically described as being caused by compression of the vertebral artery by the bony elements of the cervical spine at the atlantoaxial region during rotation of the head to the contralateral side [4]. Many cases are comorbid with atherosclerotic, stenotic, or otherwise compromised vascular anatomy [4].…”
Section: Introductionmentioning
confidence: 99%
“…RVBI is also known as Bow Hunter's Syndrome and is most classically described as being caused by compression of the vertebral artery by the bony elements of the cervical spine at the atlantoaxial region during rotation of the head to the contralateral side [4]. Many cases are comorbid with atherosclerotic, stenotic, or otherwise compromised vascular anatomy [4]. Rare cases of RVBI have been associated with other pathological mechanisms or anatomy such as bilateral rotation of the head, tilting the head, presence of distal pseudoaneurysm, osteophytes at lower cervical regions, and neck muscle hypertrophy [2,4,5].…”
Section: Introductionmentioning
confidence: 99%